Seaside Resort Blues: The English Seaside in the 1930s - Richter, Virginia (Hungarian Journal of English and American Studies, 2021)
In the interwar period, seaside holidays had become accessible to more people in the United Kingdom than ever before. It was not least the unapologetic hedonism of the working classes that gave places like Blackpool and Scarborough their vibrant energy. However, a notable number of English travelogues in the 1930s depict seaside resorts as overcrowded, vulgar, debilitating, and in fact un-English. During the years in which the UK faced the rising threat of fascism, the seaside became a site where ideas of Englishness, popular culture, and masculinity came under scrutiny. In my paper, I explore these ambivalent constructions of the English seaside resort, from J. B. Priestley’s English Journey to the collection Beside the Seaside, in which women authors, including Yvonne Cloud and Kate O’Brian, celebrate the seaside as a catalyst of female agency. (VR)